2018
DOI: 10.1124/dmd.118.083337
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Finerenone, a Novel Nonsteroidal Mineralocorticoid Receptor Antagonist, in Dogs, Rats, and Humans, In Vivo and In Vitro

Abstract: Mass balance and biotransformation of finerenone, a nonsteroidal mineralocorticoid receptor antagonist, were investigated in four healthy male volunteers following a single oral administration of 10 mg (78 Ci) of [C]finerenone and compared with data from studies in dogs and rats. The total recovery of the administered radioactivity was 101% in humans, 94.7% in dogs, and 95.2% in rats. In humans, radioactivity was mainly excreted renally (80%); in rats, it was primarily the biliary/fecal route (76%); and in dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 21 publications
2
44
0
1
Order By: Relevance
“…No clear effects on AUC or C max were seen in participants with mild hepatic impairment [9]. Crossover studies assessed the mass balance, absolute bioavailability, and effects of erythromycin, verapamil, and gemfibrozil on the systemic exposure of finerenone, complemented by in vitro studies [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…No clear effects on AUC or C max were seen in participants with mild hepatic impairment [9]. Crossover studies assessed the mass balance, absolute bioavailability, and effects of erythromycin, verapamil, and gemfibrozil on the systemic exposure of finerenone, complemented by in vitro studies [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality rates due to heart failure can be markedly reduced by treatment with certain steroids (spironolactone ( 1 ) and eplerenone ( 2 )) which block the mineralocorticoid receptor (MR) (Figure 1). [1] However, their clinical use is limited due to the significant side effects they can cause for example, hyperkalemia and worsening of kidney function [2] and so new MR antagonists are required [3] . As an alternative, it has been reported that 1,4‐dihydropyridines (DHPs), a compound class known for its Ca 2+ channel modulating activity, [4] can act as MR antagonists in vitro [5] .…”
Section: Figurementioning
confidence: 99%
“…In vitro and in vivo studies also showed that the major metabolite of amlodipine is the dehydrogenated pyridine analogue (2, Figure 1) which is primarily related to the CYP3A4 activity and none of the pyridine derivative metabolites of amlodipine have significant pharmacological activity [27]. However this metabolic route is not common, for example CYP-related metabolism of nonsteroidal antimineralocorticoid finerenone shows a similar oxidative pathway [28].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that the nature of the functional groups, the density of reactive groups and the hydrophobic/hydrophilic properties of catalyst carriers can be well-controlled by surface modifications by means binary and ternary mixtures of substituted organosilanes. The systematic combination of organosilanes provided improved immobilized biocatalysts built up from nanoparticles or nanoporous networks [16,[28][29][30][31]. MNPs with dual functions created by surface modification with binary mixtures of organosilanes (containing aminopropyl-trimethoxy silane:methyl-trimethoxysilane mixtures at molar ratios of 1:0, 1:1, 1:4, 1:16 and 0:1) had not previously been investigated yet for the immobilization of metalloporphyrins.…”
Section: Introductionmentioning
confidence: 99%